MSME PERCEPTION OF FINANCIAL TECHNOLOGY (FINTECH) IN BANYUWANGI DISTRICT - Suprihatin, Endang; Mahendra, Andhika (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Development of Fintech in Indonesia in particular has become one of the ideas to conduct research in this field, especially in Banyuwangi Regency, especially now that business actors are in the healing phase after being sick due to the impact of the Covid pandemic storm, the effort to rise is by trying to rise again. back from adversity, which previously did not produce goods, now is the time to return to operations, by mobilizing all resources, especially capital resources which automatically triggers business actors to get capital financing assistance in an easy way, with the number of MSMEs increasing significantly starting in 2018 which is 122% , is a target for Fintech companies to provide assistance in the form of capital, one solution to the problem of MSMEs is the many offers that are obtained via cellphones, namely SMS, Whats up, even flyers and banners scattered on the streets and in the media. all social luring anyone, especially business actors, to borrow money for business capital. This research is a qualitative descriptive to obtain information on how the Banyuwangi MSME actors perceive Financial Technology (Fintech), by taking information from 4 business informants in Banyuwangi, the result is that all MSMEs have been offered loans by Fintech and most of them have become victims of the Peer Fintech type. to peer landing which is known as Pinjol (online loan) and Fintech type Equity crowd funding or fraudulent investment, so that the victim ’s name is tainted so that it has a psychological and social impact, therefore the role of the government is needed in providing socialization to the public about financial technology (Fintech), as well as legal and illegal Fintech characteristics so that negative impacts can be handled to a minimum.